(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Krosnolutskiy K. K. Interpretation definitions of «critical thinking»: historical background. Thе article analyzes the concept «critical thinking». The history of the development and evolution of the study of «critical thinking», the main stages in the development of critical thinking and evaluation of its development levels are considered in the scientific literature. At this stage there was made the analysis of definitions: 1) psychological readiness to consider carefully the issues and questions that are part of the own life experience, 2) knowledge of the methods of research and logical reasoning 3) the presence of certain skills in these methods application.